2019
DOI: 10.1016/j.isci.2019.06.004
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Planar Perovskite Solar Cells with Negligible Hysteresis Using 2,2,2-Trifluoroethanol-Incorporated SnO2

Abstract: Summary An efficient electron transport layer (ETL) between the perovskite absorber and the cathode plays a crucial role in obtaining high-performance planar perovskite solar cells (PSCs). Here, we incorporate 2,2,2-trifluoroethanol (TFE) in the commonly used tin oxide (SnO 2 ) ETL, and it successfully improves the power conversation efficiency (PCE) and suppresses the hysteresis of the PSCs: the PCE is increased from 19.17% to 20.92%, and the hysteresis is largely reduced to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 55 publications
0
61
0
Order By: Relevance
“…Instead, the Bi‐SnO 2 film exhibited the highest transmittance in the UV‐range, which is likely due to the stronger light propagation and photon oscillation at the ITO/SnO 2 interface with increasing film thickness. [ 38 ] To further verify this, a simple finite‐difference time‐domain simulation has been conducted to calculate the optical transmittance spectra of the nanostructured SG‐SnO 2 , NP‐SnO 2 , and Bi‐SnO 2 films on ITO substrate. The detailed simulation method and input parameters can be found in Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, the Bi‐SnO 2 film exhibited the highest transmittance in the UV‐range, which is likely due to the stronger light propagation and photon oscillation at the ITO/SnO 2 interface with increasing film thickness. [ 38 ] To further verify this, a simple finite‐difference time‐domain simulation has been conducted to calculate the optical transmittance spectra of the nanostructured SG‐SnO 2 , NP‐SnO 2 , and Bi‐SnO 2 films on ITO substrate. The detailed simulation method and input parameters can be found in Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…This result may stem from that Sn 4+ metal atom coordinate with two more mono‐dentate halogen ligands in Cl 2 /Br 2 than tin(II) bis(acetylacetonate). Moreover, Luan et al also observed that oxygen plasma treatment of the SnO 2 film surface can significantly improve device performance, possibly attributed to changes in surface roughness and work function …”
Section: Passivation Of Carrier Transport Layermentioning
confidence: 99%
“…[ 9 ] TiO 2 and SnO 2 , the most promising ETMs in planar PSCs, are not always ideal for efficient charge extraction due to their low electron mobility, large energy barrier, and vast uncoordinated defect sites. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%